Getting past "the pimp" : management in the sex industry - Bruckert, Chris, 1960-; Parent, Colette, 1947- (University of Toronto Press, 2018)
Getting Past ""the Pimp"" makes a compelling case for rethinking Canada's response to sex work by highlighting the limits of criminal justice solutions and drawing our attention to the experiences and perspectives of those targeted.